The Efficacy of Using Contextual Teaching and Learning (CTL) Approach in Teaching Speaking to Indonesian English as Foreign Language (EFL) Students - Yanpitherszon Liunokas (Institut Agama Islam Negeri Palopo, 2023)
This research aims at finding out the efficacy of using Contextual Teaching and Learning (CTL) approach in teaching speaking especially describing to Indonesian English as Foreign Language (EFL) students. The main question of this research: Is the use of Contextual Teaching and Learning (CTL) approach effective in teaching speaking to Indonesian EFL students? The research can be an addition to the persisting teaching speaking in English through the use of Contextual Teaching and Learning (CTL) approach. This research was conducted at First semester students of the English Study Program of Nusa Cendana University, Kupang. The population of this research was First semester students of the English Study Program of Nusa Cendana University, Kupang. The number population is 160 in four classes. The research used a pre-experimental method with a pre-test and post-test design. The pre-test was given to find out the basic ability of the students in mastering speaking and the post-test given to find out the students’ improvement in mastering speaking after giving the treatment by using problem solving approach. The findings show that using problem solving is effective in teaching speaking to Indonesian EFL students. It is supported by the result of the significance test through SPSS 20 program that the P was 0.00. Therefore, it is recommended to use problem solving approach in developing students’ speaking of Indonesian EFL students.